Design of Smart Fuel Station and Management System Based on Arduino and Internet of Things - Budi Prijo Sembodo; Haris Atmajaya (BEST, 2021)
Patrol that is distributed to the public must meet the requirement for the quality, quantity and continuity. Pertamina as one of the companies that is responsible for the distribution of patrol to the public through gas stations and must have competent management and services. However, problems arise in the community and even companies in controlling fuel consumption and queues for sales services at gas stations. One solution is to use a station that is connected to smartphone wirelessly and a cashless. Through the "Smart Fuel Station and Management System Based on Arduino and Internet Of Things", that will be able to help the community and companies in controlling their fuel consumtion and making savings. This monitoring tool uses the Arduino ESP8266 which is combined with Internet of Things (IoT) Technology which is displayed on the LCD and the Internet Web. Customers can purchase the patrol at gas stations independently, by connecting the smartphone application with the gas station wireless and purchase and make payments through the application. By having top up the balance on the application to be able to make purchases as needed and the balance will continue to decrease according to usage. The fuel filling station will issue it according to the nominal or the number of liters we choose in the application. Customers can view detailed fuel purchase for place, date, time, amount and total balance.